The Role of Perceived Organizational Support in Enhancing Innovative Work Behavior among Vocational School Teachers - Maharani, Apriana Dewi; Izzati, Umi Anugerah (Journal of English Language and Education, 2026)
This research investigates the connection between perceived organizational support (POS) and innovative work behavior (IWB) among teachers at SMK Negeri X in Surabaya. POS denotes educators' opinions of the school's appreciation for their contributions and concern for their personal and professional welfare, whereas creative work behavior encompasses the creation, promotion, and execution of novel ideas in pedagogy and learning. The research hypothesized a significant positive relationship between POS also innovative work behavior. The product moment correlation test was used in a quantitative correlational scheme. Participants were 72 teachers selected through purposive sampling. Data were gathered utilizing a POS scale derived from Rhoades and Eisenberger (2002) and a novel work behavior measure modified from De JongDen Hartog (2010). This finding revealed a substatial value below 0.001 and a correlation coefficient of 0.609, signifying a robust positive impact across the variables. These findings indicate that organizational support correlates with innovation.